2022
DOI: 10.1029/2021gl095276
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Pan‐Arctic Peatland Carbon Dynamics Under Alternative Warming Scenarios

Abstract: Peatlands are considered one of the biggest carbon reserves in the terrestrial ecosystem, comprising 30% of the present-day soil organic carbon pool (Yu, 2012). They are also a major source of methane (CH 4 ), a potent greenhouse gas (Abdalla et al., 2016). They are transitional zones between upland mineral soils and wetland ecosystems (Loisel et al., 2017). High latitude peatlands constitute unique habitats with many special characteristics such as shallow water table depth, organic soils, distinct vegetation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…Increased ER under the warming scenarios, due to higher AT and lower water tables, resulted in further reductions of NEP, causing the site to function as a progressively stronger source of CO 2 to the atmosphere under warmer conditions. Similar reductions in peatland NEP resulting from increased ER under warmer future climate scenarios have also been projected for northern latitude peatlands (Chaudhary et al, 2022), many of which contain similar plant communities to those found in the Rocky Mountains. The site was a source of CH 4 under all three climate scenarios, and growing season efflux showed a slight decrease under the warming climate scenarios, resulting from lower NEP, which was driven by greater increases in ER relative to GPP.…”
Section: Discussionsupporting
confidence: 61%
“…Increased ER under the warming scenarios, due to higher AT and lower water tables, resulted in further reductions of NEP, causing the site to function as a progressively stronger source of CO 2 to the atmosphere under warmer conditions. Similar reductions in peatland NEP resulting from increased ER under warmer future climate scenarios have also been projected for northern latitude peatlands (Chaudhary et al, 2022), many of which contain similar plant communities to those found in the Rocky Mountains. The site was a source of CH 4 under all three climate scenarios, and growing season efflux showed a slight decrease under the warming climate scenarios, resulting from lower NEP, which was driven by greater increases in ER relative to GPP.…”
Section: Discussionsupporting
confidence: 61%
“…A new peatland and permafrost formulation with a unique representation of subgrid spatial heterogeneity was implemented in LPJ-GUESS (Chaudhary et al, 2017a), which includes dynamic annual multi-layer peat accumulation, freezing-thawing cycles and lateral flow. In previous studies (Chaudhary et al, 2018;Chaudhary et al, 2020;Chaudhary et al, 2022), we have demonstrated that the mechanistic multilayer peat accumulation scheme is quite robust and simulates reasonable vegetation dynamics, permafrost distribution, peat accumulation and dominant plant types across the pan-Arctic region. The current scheme consists of many key variables and interactions controlling the non-linear peatland dynamics as shown in our previous studies (Chaudhary et al, 2017a, Chaudhary 2018).…”
Section: Model Descriptionmentioning
confidence: 83%
“…Because of high uncertainty and large temporal and spatial variations in the relationship among temperature, precipitation, and peatland WT, it is challenging to forecast the direction and magnitude of C response of northern peatlands and their feedback with climate. However, studies including climate change predict that northern peatlands will reduce their C sink capacity (Chaudhary et al, 2020 ) or lose C (Treat et al, 2021 ; Wu et al, 2013 ) especially under strong warming scenarios (Chaudhary et al, 2022 ; Qiu et al, 2022 ). Although the magnitude of C loss in response to WT changes in our study is less than the previously studied temperature and precipitation responses, our results indicate that drying may exacerbate C loss due warming of northern peatlands.…”
Section: Discussionmentioning
confidence: 99%